The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1007/bf02310330
|View full text |Cite
|
Sign up to set email alerts
|

Altered diastolic function in infants of mothers with gestational diabetes: No relation to macrosomia

Abstract: In a previous study, asymptomatic infants of mothers with gestational diabetes (IGDMs) were observed to have altered left ventricular (LV) filling. In the present study, we reanalyzed the data to examine whether the observed abnormalities were related to maternal diabetes or due to the greater preponderance of macrosomic infants (32%) in the gestational diabetes group. No echocardiographic (systolic or diastolic) differences were observed when the data were compared in 16 large-for-gestational-age (LGA) and 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…It is unclear whether macrosomic infants born to non-diabetic mothers also demonstrate these findings. In a previous study, Mehta et al [6] found that macrosomic infants of diabetic mothers demonstrated a smaller left ventricular volume during systole and diastole than macrosomic infants born to non-diabetic mothers. They concluded that the cardiac findings observed in macrosomic infants born to diabetic mothers were related to an abnormal intrauterine environment rather than the macrosomia per se.…”
Section: Introductionmentioning
confidence: 93%
“…It is unclear whether macrosomic infants born to non-diabetic mothers also demonstrate these findings. In a previous study, Mehta et al [6] found that macrosomic infants of diabetic mothers demonstrated a smaller left ventricular volume during systole and diastole than macrosomic infants born to non-diabetic mothers. They concluded that the cardiac findings observed in macrosomic infants born to diabetic mothers were related to an abnormal intrauterine environment rather than the macrosomia per se.…”
Section: Introductionmentioning
confidence: 93%
“…Mehta et al (19) observed no differences between macrosomic and non-macrosomic IDM by echocardiography, while Demiroren et al (20) reported that LVMI was the most important echocardiographic measurement for distinguishing macrosomic infants of diabetic and non-diabetic mothers. Akcakus et al (15) found an increased LVMI in macrosomic IDM.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we have no reason to expect relaxation abnormalities in the IDDM fetus. It has been demonstrated that asymptomatic infants of mothers with diabetes mellitus also have altered ventricular filling 11 . Analysis of left ventricular filling parameters and upper abdominal circumference suggests that the cardiac alterations are not due to the preponderance of macrosomia but rather are the consequence of an altered in utero metabolic environment.…”
Section: Discussionmentioning
confidence: 99%
“…In pregnancies associated with diabetes, chronic fetal hyperinsulinemia may occur, causing increased total body weight and selective organomegaly as a result of hypertrophy of insulin-sensitive tissues 8,9 . In the presence of fetal macrosomia, cardiac weight is increased, owing to a larger mass of myocardial nuclei, increased cell number and increased myocardial fiber 10 . However, besides hypertrophy, reduced left ventricular filling has been shown in infants of mothers with gestational diabetes 11 .…”
Section: Introductionmentioning
confidence: 99%